Analisis laporan keuangan mengenai pengaruh profitabilitas sebagai strategi bisnis pada bank ganesha - difri, fanesa ainun (Maliki Interdisciplinary Journal, 2025)
This research analyzes Bank Ganesha's financial reports for the period 2020 to 2023 to evaluate the influence of profitability as a business strategy. The method used is comparative analysis with a focus on financial ratios, including profitability, liquidity, activity and solvency ratios. The analysis results show a positive trend in the bank's financial performance, with a significant increase in profitability ratios. Despite fluctuations in liquidity ratios, the bank demonstrated efforts to strengthen its cash position. Solvency ratios also showed improvement, reflecting better debt and capital management. This research provides important insights for investors and stakeholders regarding the financial health of Bank Ganesha.